Development of nitrocellulose membrane filters impregnated with different biosynthesized silver nanoparticles applied to water purification - Fernández, Jorge Gastón (2015)
Bactericidal water filters were developed. For this purpose, nitrocellulose membrane filters were impregnated with different biosynthesized silver nanoparticles. Silver nanoparticles (AgNPs) from Aspergillus niger (AgNPs-Asp), Cryptococcus laurentii (AgNPs-Cry) and Rhodotorula glutinis (AgNPs-Rho) were used for impregnating nitrocellulose filters. The bactericidal propertie of these nanoparticles against Escherichia coli, Enterococcus faecalis and Pseudomona aeruginosa were successfully demonstrated. The higher antimicrobial effect was observed for AgNPs-Rho. This fact would be related not only to the smallest particles, but also to polysaccharides groups that surrounding these particles. Moreover, in this study, complete inhibition of bacterial growth was observed on nitrocellulose membrane filters impregnated with 1mgL-1 of biosynthesized AgNPs. This concentration was able to reduce the bacteria colony count by over 5 orders of magnitude, doing suitable for a water purification device.